(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
In this article, we first present a theoretical study on the status and origin of the conceptions.Then, based on this study, we make a quantitative and, at the same time, a qualitative analysis of the responses of 148 students to a questionnaire on the notion of convergence of numerical sequences. The results of the experiment show that the errors of the students come mostly from previous incorrect conceptions. We think that the traditional teaching method favors the emergence of these conceptions and that the introduction of new teaching methods is needed. Besides the difficulties noted in the resolution of exercises, the composition of answers reveals to us severe language problems related to French expressions, which, in turn, require a reflection on a more adequate content of the teaching of the French language in the first years of university science tracks.